2020
DOI: 10.1021/acschemneuro.0c00535
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of the Effect of Neurokinin B on Toxic Aβ Aggregates in Alzheimer’s Disease with the Molecular Mechanisms’ Action

Abstract: Clinical trials of past and current treatments for Alzheimer's disease (AD) patients on the market suffer from the dual drawbacks of a lack of efficacy and side effects. Neuropeptides have been highlighted by their potential to protect cells against AD and can reverse the toxic effect induced by Aβ in cultured neurons. One of the neuropeptides that has insufficient attention in the literature as a potential treatment for prevention of the progression of AD is neurokinin B (NKB). There are critical and unresolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Since the Aβ(1–40) effects were mimicked by antagonists of tachykinin receptors, the authors rationalized their experimental data in terms of Aβ(1–40) binding to these receptors [ 17 ]. Substance P has been found in Aβ plaques of patients with Alzheimer’s disease [ 124 , 125 ], a result that suggests strong interactions between Aβ and substance P. Later, coincubation studies between kassinin and Aβ(25–35), as well as between substance P and Aβ(25–35), reported to foster Aβ aggregation and fibrils formation [ 126 ], but a computational study predicts that neurokinin B should inhibit the formation of Aβ(25–35) dimers [ 127 ]. More recently, Liu et al [ 22 ] reported that neurokinin B and substance P remove the Aβ(25–35) hexamers and dodecamers, which are related to its toxicity, although substance P did so more slowly, and, in contrast, kassinin was found to promote the formation of these higher-order oligomers.…”
Section: Brain Peptides That Have Been Experimentally Demonstrated To...mentioning
confidence: 99%
“…Since the Aβ(1–40) effects were mimicked by antagonists of tachykinin receptors, the authors rationalized their experimental data in terms of Aβ(1–40) binding to these receptors [ 17 ]. Substance P has been found in Aβ plaques of patients with Alzheimer’s disease [ 124 , 125 ], a result that suggests strong interactions between Aβ and substance P. Later, coincubation studies between kassinin and Aβ(25–35), as well as between substance P and Aβ(25–35), reported to foster Aβ aggregation and fibrils formation [ 126 ], but a computational study predicts that neurokinin B should inhibit the formation of Aβ(25–35) dimers [ 127 ]. More recently, Liu et al [ 22 ] reported that neurokinin B and substance P remove the Aβ(25–35) hexamers and dodecamers, which are related to its toxicity, although substance P did so more slowly, and, in contrast, kassinin was found to promote the formation of these higher-order oligomers.…”
Section: Brain Peptides That Have Been Experimentally Demonstrated To...mentioning
confidence: 99%
“…The mechanisms by which neurokinin B affects the inhibition of Aβ aggregation are still unknown. 17,18 Amyloid A is actively included in the pathological processes of rheumatoid arthritis, cancer, atherosclerosis, and AD by its collection. The apolipoprotein family includes the highly conserved protein amyloid A, which is mostly produced by the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Substance P, a neurotransmitter associated with inflammatory responses and pain, is found in the brain, is able to form fibrils in the presence of heparin, and has been found in Aβ plaques of patients with Alzheimer’s disease. , This suggests strong interactions between Aβ and Substance P. Although all these peptides form fibrils, Substance P, NK, and Kassinin are non-toxic during fibril formation in cell studies, unlike Aβ(25–35), which is related to Alzheimer’s disease. , Furthermore, it has been reported that Substance P, NK, and Kassinin are able to reduce the neurotoxicity of Aβ(25–35) in animal studies and in cells. ,, Two coincubation studies between Kassinin and Aβ(25–35) and also between Substance P and Aβ(25–35) suggested an acceleration of amyloid formation for all three peptides . Also, a computational study predicts that NK inhibits the formation of Aβ(25–35) dimers . However, the molecular mechanisms of how these tachykinin neuropeptides affect the aggregation of Aβ(25–35) are unknown.…”
Section: Introductionmentioning
confidence: 99%